2011
DOI: 10.1111/j.1530-0277.2011.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 and ADH1B Interactions in Retrospective Reports of Low-Dose Reactions and Initial Sensitivity to Alcohol in Asian American College Students

Abstract: Background A mechanistic model has been proposed for how alcohol metabolizing gene variants protect individuals from the development of alcohol use disorders, with heightened sensitivity to alcohol being an early step (endophenotype) in this model. The present study was designed to determine whether possession of two alcohol metabolizing genes variations, the aldehyde dehydrogenase ALDH2*2 allele and the alcohol dehydrogenase ADH1B*2 allele, was associated with self-reported sensitivity to alcohol at low doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
(81 reference statements)
0
27
0
Order By: Relevance
“…About 44% of subjects reported that most or all of their friends got drunk. Because ALDH2 *2/*2 carriers are more sensitive to alcohol (31,32), differences between ALDH2 *2/*2 and ALDH2 *1/*2 were also evaluated. The two genotypes were similar ( p > .05) on all study variables, including alcohol consumption, t ( 97 ) = − 1.04, p = .300, and number of friends who got drunk, χ 2 (4, 100) = 1.81, p = .771.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 44% of subjects reported that most or all of their friends got drunk. Because ALDH2 *2/*2 carriers are more sensitive to alcohol (31,32), differences between ALDH2 *2/*2 and ALDH2 *1/*2 were also evaluated. The two genotypes were similar ( p > .05) on all study variables, including alcohol consumption, t ( 97 ) = − 1.04, p = .300, and number of friends who got drunk, χ 2 (4, 100) = 1.81, p = .771.…”
Section: Resultsmentioning
confidence: 99%
“…For example, while ALDH2 *2(−) carriers may be more susceptible to the permissive norms for drinking associated with higher levels of peer drunkenness in college settings, ALDH2 *2(+) carriers may be less so because of the negative consequences of drunken behavior, which can include students vomiting or passing out in public places (28). ADLH2 *2(+) carriers may be more deterred by these instances, as the protective effects of ALHD2 *2(+) in reducing drinking include such adverse reactions as nausea and drowsiness that can, for some individuals, occur after only 1 to 2 drinks (31,32). Seemingly in support of this, Hendershot et al (38) found that carriers of ALDH2 *2(+) report higher negative alcohol expectancies and physiological expectancies such as dizziness and nausea compared to carriers of ADLH2 *2(−).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic genome-wide scan in the same Native American sample identified regions of interest on chromosomes 6, 10, 12, and 17 that were associated with participants’ self-reported subjective LR early in their drinking careers [53]. Variation in the aldehyde dehydrogenase gene (ALDH2) on chromosome 12 was associated with self-reported subjective LR early in the drinking careers of a sample of Chinese- and Korean-American college students [54]. Finally, variants in the cholinergic nicotinic receptor gene cluster ( CHRNA5-CHRNA3-CHRNB4) on chromosome 15 [55, 56] and genes sets implicated in neuronal signaling [57] were associated with LR in a sample of young adult offspring of alcoholics.…”
Section: Evaluating the Weight Of Evidence For Aud Candidate Endophenmentioning
confidence: 99%
“…The protective effects for AUDs (but not SUDs) from some variations in genes that produce the major alcohol-metabolizing enzymes have long been known Eng et al, 2007;Hubacek et al, 2012;Li et al, 2011;Luczak et al, 2011). One example is a mutation seen in about 40% of Asians in the gene producing the enzyme aldehyde dehydrogenase (ALDH) that is responsible for the metabolism of the fi rst breakdown product of alcohol, acetaldehyde.…”
Section: Current Studies Of Genetic and Environmental Contributors Tomentioning
confidence: 99%